INFORMATION SYSTEM APPLICATION DEVELOPMENT: A CASE STUDY OF CV. BULUK LUPA SME - Irfan Ardiansah; Rahmat Subrata Kardaya; Devi Maulida Rahmah; Selly Harnesa Putri; Ryan Hara Permana (Indragiri Islamic University, 2023)
This study involves the creation and deployment of a Laravel framework-based web-based management information system for a business entity referred to as Buluk Lupa. The website serves as a platform for all transactions in Buluk Lupa, as well as a medium for promotion and storage of product and stock data online. The website employs a bootstrap with the Magenta theme, organizing the appearance of the website like a table while also providing separate pages for each menu item. The website also includes a shopping cart feature for users to purchase products, as well as a cookie system to streamline the user experience during login and order placement. The website underwent black box testing to ensure all functions align with the intended requirements. The text also discusses the economic feasibility analysis of Buluk Lupa's products and the proposed system modifications to make the existing information system more effective and provide a positive impact on sales and data collection, affecting Buluk Lupa's growth.